2016
DOI: 10.1007/s10519-016-9789-z
|View full text |Cite
|
Sign up to set email alerts
|

Person-Specific Non-shared Environmental Influences in Intra-individual Variability: A Preliminary Case of Daily School Feelings in Monozygotic Twins

Abstract: Most behavioural genetic studies focus on genetic and environmental influences on inter-individual phenotypic differences at the population level. The growing collection of intensive longitudinal data in social and behavioural science offers a unique opportunity to examine genetic and environmental influences on intra-individual phenotypic variability at the individual level. The current study introduces a novel idiographic approach and one novel method to investigate genetic and environmental influences on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Adolescents' affects are naturally impacted by these daily events and go up and down consequently as these events come and go. It is, thus, not surprising that η is predominantly explained by non‐shared environment: daily events are largely idiosyncratic and unique to each person (Burt et al., 2015; Zheng & Asbury, 2019; Zheng, Molenaar, et al., 2016). As opposed to these uncontrollable daily events, however, when facing environmental experiences that change our affect, what people can control more proactively is how quickly or gradually their affect returns to the equilibrium following any disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescents' affects are naturally impacted by these daily events and go up and down consequently as these events come and go. It is, thus, not surprising that η is predominantly explained by non‐shared environment: daily events are largely idiosyncratic and unique to each person (Burt et al., 2015; Zheng & Asbury, 2019; Zheng, Molenaar, et al., 2016). As opposed to these uncontrollable daily events, however, when facing environmental experiences that change our affect, what people can control more proactively is how quickly or gradually their affect returns to the equilibrium following any disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, our study is the largest regarding the sample size and time length of all twin studies with similar designs. Moreover, among extant scant twin studies using genetically informative intensive longitudinal data, few have examined affective dynamics in children and adolescents (Burt et al., 2015; Zheng, Molenaar, et al., 2016), while the majority focused on adults (Jacobs et al., 2006, 2013). Nonetheless, our sample size is admittedly smaller compared to other conventional twin studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By inspecting the results across the different twin pairs, the iFACE model can be used to get an impression of the differences between twin pairs in the processes and heritabilities when the iFACE model. For example, Zheng et al (2016) applied the iFACE model separately to the daily positive and negative school feelings of multiple 10-year-old MZ twin pairs. They found that the amount of variance in the daily fluctuations in these feelings that was due to unique environmental influences varied greatly across twin pairs.…”
Section: Iface Modelmentioning
confidence: 99%